Younger Age and Albuminuria are Associated with Proliferative Diabetic Retinopathy and Diabetic Macular Edema in the South Indian GeNetics of DiAbeTic Retinopathy (SIGNATR) Study. (3rd October 2022) - Susarla, Gayatri; Rizza, A.N.; Li, Ashley; Han, Samuel; Khan, Rehana; Chan, Weilin; Lains, Ines; Apivatthakakul, Atitaya; Brustoski, Kim; Khetan, Vikas; Raman, Rajiv; Igo, Robert P.; et al.
Abstract: Purpose: The purpose of the South Indian GeNetics of DiAbeTic Retinopathy (SIGNATR) Study is to identify non-genetic and genetic risk factors associated with diabetic retinopathy (DR). This report examines the non-genetic risk factors for DR in South Indian patients. Methods: Participants with South Indian ancestry and type 2 diabetes (T2D) were included from two sources: the Sankara Nethralaya Diabetic Retinopathy and Molecular Genetics Study (SN-DREAMS) and prospective recruitment at Sankara Nethralaya affiliates. Fundus photography and optical coherence tomography (OCT) were obtained on participants. Fundus images were graded for DR severity and OCTs were graded for center-involved diabetic macular edema (ciDME). Multivariate analyses were performed using stepwise logistic regression to assess effects of the demographic and clinical factors on proliferative DR (PDR) and DME. Results: Among the 2941 participants with DR grading, participants with PDR were more likely to be younger [odds ratio (OR)=0.95], men (OR = 1.83), have a longer duration of diabetes (OR = 1.10), have a higher hemoglobin A1c (OR = 1.12), have albuminuria (OR = 5.83), have hypertension (OR = 1.69), have a higher HDL (OR = 1.02) and a lower total cholesterol (OR = 0.99) (all p < 0.05). Among the 483 participants with gradable OCT scans, participants who had ciDME were more likely to be younger (OR = 0.97), men (OR = 2.80), have a longer duration of diabetes (OR = 1.06), have lower triglycerides (OR = 0.99), and have albuminuria (OR = 3.12) (all p < 0.05). Conclusions: Younger age, male sex, longer duration of diabetes, higher HbA1c, and presence of albuminuria were identified as risk factors for PDR and DME in a South Indian population with T2D.